Mapping The Digital Frontier: A Bibliometric Exploration Of Heritage Preservation Technologies - Noor Farhana Alias; Nurul Syala Abdul Latip; Noor Hayati Ismail; Osama Elrawi (Global Academic Excellence, 2026)
Non-Indexed Publication